Bildung as an essential disposition in becoming a reflective practitioner: practical application of philosophical hermeneutics to second language teacher education. Issue 3 (4th May 2018) - Yagata, Katsuhide
Abstract: For a few decades, reflective practice has been employed in second language teacher education (SLTE) as 'a means by which practitioners can develop a greater level of self-awareness about the nature and impact of their performance, an awareness that creates opportunities for professional growth and development'. Dewey, who initiated the concept of reflective thinking in teacher education, emphasized one's attitudes toward engagement in reflective process. One such disposition is open-mindedness, 'a willingness to entertain different perspectives… and acknowledgement of the limitations of one's own perspectives'. Regarding this concept of open-mindedness, Gadamer, who established philosophical hermeneutics, provided profound insights by using the German word Bildung, which is often translated as education, culture, or self-cultivation. Through this concept, Gadamer emphasized not only one's open and introspective disposition toward new experience but also one's mode of being. This paper explores this notion of Bildung and examines its possible practical application to SLTE in combination with reflective practice. Referring to Grondin's notion that education is to raise true questions, I will argue for the importance of nurturing Bildung of preservice second language teachers and of second language teacher educators.